1993
DOI: 10.1021/ma00058a001
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and polymerization of alkyl 1-bicyclobutanecarboxylates

Abstract: Bicyclobutane monomers substituted with an ester group at the 1 position were synthesized using a practical synthesis route, starting from 1,1 -cyclobutanedicarboxylic acid, which is adaptable to the synthesis of various bicyclobutane esters and can be scaled up. Four new bicyclobutane monomers were prepared using this method, namely ethyl, isopropyl, ß,ß,ß-trifluoroethyl, and phenyl 1-bicyclobutanecarboxylate. These bicyclobutanecarboxylates were subjected to free radical polymerization under various conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 3 publications
2
32
1
Order By: Relevance
“…It has a bond strain energy of 66 kcal/mol, more than double the value of either cyclopropane or cyclobutane (Ϸ26 kcal/mol) (23). Extensive efforts have been made during the past 40 years to develop synthetic approaches to molecules containing a bicyclobutane subunit and to understand the chemistry of this structure (24)(25)(26)(27) Fig. 2.…”
Section: Discussionmentioning
confidence: 99%
“…It has a bond strain energy of 66 kcal/mol, more than double the value of either cyclopropane or cyclobutane (Ϸ26 kcal/mol) (23). Extensive efforts have been made during the past 40 years to develop synthetic approaches to molecules containing a bicyclobutane subunit and to understand the chemistry of this structure (24)(25)(26)(27) Fig. 2.…”
Section: Discussionmentioning
confidence: 99%
“…Methyl bicyclobutane-1-carboxylate (MBCB) was prepared according to the procedures reported previously, 3,15 and purified prior to polymerization by distillation over calcium dihydride under reduced nitrogen pressure. Toluene and heptane were purified in the usual manner, mixed with a small amount of n-butyllithium and distilled under high vacuum just before use.…”
Section: Methodsmentioning
confidence: 99%
“…3 Anionic polymerization offers potentially better control of stereochemistry of polymers, but early attempts for methyl bicyclobutane-1-carboxylate (MBCB) with n-butyllithium as an initiator gave only low molecular weight products. In the previous paper, 4 we reported the anionic polymerization of MBCB with tert-butyllithium (t-BuLi)/bis(2,6-di-tertbutylphenoxy)ethylaluminum [EtAl(ODBP) 2 ] in toluene at À78 C gave transtactic polymers (trans contents > 90%) in high yields.…”
mentioning
confidence: 99%
“…Drujon 9 reported that poly(methyl bicyclobutanecarboxylate) showed a surprisingly low T g , namely 95°C compared to the T g of PMMA. Molecular mechanics calculation on poly(methyl bicyclobutane-1-carboxylate) fragments revealed an unexpected high flexibility of the bicyclobutane polymer backbone.…”
Section: Characterizations Of the Polymersmentioning
confidence: 99%
“…6 In further work they synthesized four monomers, i.e., ethyl, isopropyl, ␤,␤,␤-trifluoroethyl, and phenyl 1-bicyclobutanecarboxylate. [7][8][9] The temperature, the size of ester group, or the nature of the initiator had no marked influence on the stereochemistry of the bicyclobutane polymer backbones. Poly(methyl 1-bicyclobutanecarboxylate) is an optically clear material and shows excellent thermal degradation resistance, but all these polymers exhibit surprisingly low T g s compared to poly(1-cyanocyclobutane).…”
Section: Introductionmentioning
confidence: 99%